Facile access to potent antiviral quinazoline heterocycles with fluorescence properties via merging metal-free domino reactions - Felix E. Held (Nature Portfolio, 2017)
Heterocycles are ubiquitous in bioactive compounds and routes to different substitution patterns are important to access the full substrate space. Here the authors report a route to 4,5,7,8-substituted antiviral fluorescent quinazolines, to allow cellular uptake visualization without external marker.